(untitled) (Research, Society and Development, 2020)
This study aimed to develop cooking workshops using less preferred foods by schoolchildren and to evaluate their sensory acceptability and physico-chemical composition. A total of 1,010 children (7 and 10 years old) enrolled in 10 public schools in Guarapuava, PR. Children’s food preference was assessed using a self-administered questionnaire. Food preparations containing the 10 foods least preferred by children have been prepared. Culinary workshops were applied with these products, being evaluated in relation to their sensorial acceptability and physico-chemical composition. The less preferred foods were eggplant (77.6%) and melon (52.5%). The chayote brigadeiro, zucchini cupcake and melon mousse received the highest marks in all sensory attributes and for global acceptance. All preparations presented high levels of acceptability (> 70%). Higher moisture contents and lower ash, carbohydrates, calories and fibers were observed in the melon mousse. Higher levels of ashes, proteins and carbohydrates were verified for eggplant chips, while cress patty and chard pie had the highest lipid contents. Eggplant chips and lentil hamburger had the highest amounts of fiber. It is concluded that changes in the preparation form increase the sensory acceptability of nutritious foods that have a high rejection rate for school children, such as vegetables and fruits. This effect occurs mainly when these changes are associated with a learning strategy such as the cooking workshop.